2021
DOI: 10.3233/nre-210034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of robot-assisted gait training on cortical activation in stroke patients: A functional near-infrared spectroscopy study

Abstract: OBJECTIVE: To investigate the effects of the robot–assisted gait training on cortical activation and functional outcomes in stroke patients. METHODS: The patients were randomly assigned: training with Morning Walk® (Morning Walk group; n = 30); conventional physiotherapy (control group; n = 30). Rehabilitation was performed five times a week for 3 weeks. The primary outcome was the cortical activation in the Morning Walk group. The secondary outcomes included gait speed, 10-Meter Walk Test (10MWT), FAC, Motric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It suggests that RAT can attenuate limb spasms caused by upper motor neuron disease, associated with repetitive motion and drafting ( Veerbeek et al, 2017 ; Cho et al, 2018 ; Cho and Song, 2019 ). In addition, Song et al (2021) confirmed that RAT could improve motor function and stimulate cortical activation, revealing the other mechanism involved in RAT. A multicentric, randomized controlled trial conducted in Britain compared RAT effectiveness, enhanced upper limb therapy, and usual care.…”
Section: Robot-assisted Therapymentioning
confidence: 71%
“…It suggests that RAT can attenuate limb spasms caused by upper motor neuron disease, associated with repetitive motion and drafting ( Veerbeek et al, 2017 ; Cho et al, 2018 ; Cho and Song, 2019 ). In addition, Song et al (2021) confirmed that RAT could improve motor function and stimulate cortical activation, revealing the other mechanism involved in RAT. A multicentric, randomized controlled trial conducted in Britain compared RAT effectiveness, enhanced upper limb therapy, and usual care.…”
Section: Robot-assisted Therapymentioning
confidence: 71%
“…If motor imagery was correctly identified, the robot gave visual and movement feedback by actually moving the paretic hand. MorningWalk ® system for gait recovery [ 47 ]. This was created in 2014 by CUREXO Inc. in Korea for the rehabilitation of individuals with gait disorders.…”
Section: Resultsmentioning
confidence: 99%
“…MorningWalk ® system for gait recovery [ 47 ]. This was created in 2014 by CUREXO Inc. in Korea for the rehabilitation of individuals with gait disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As rehabilitation progressed, increased PMC activation was found in the affected side after 2 months of TW training, and the asymmetry of bilateral SMC activation was improved ( 35 ). Song et al reported that cortical activation in patients with stroke was lower in the affected hemisphere than in the unaffected one, while asymmetric activation performance was improved after 3 weeks of robot-assisted gait training ( 42 ). Similarly, our research also found asymmetric cortical activation during hemiplegic walking, improved bilateral activation during FES-assisted hemiplegic walking in patients with post-stroke, and speculated that a new interhemispheric balance may be re-established by activating specific brain regions in SMA and PMC on the affected side.…”
Section: Discussionmentioning
confidence: 99%